2014
DOI: 10.1007/s10948-014-2821-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ag Addition on the Superconducting Properties of FeSe0.94

Abstract: The tetragonal FeSe phase is an intensively investigated iron based superconductor. In this study we examined the influence of Ag addition on the superconducting properties of selenium deficient polycrystalline FeSe 0.94 . The samples were obtained by solid state reaction and melting methods. XRD analysis shows the presence of tetragonal phase and EDX analysis establishes inhomogeneous Ag distribution in the grains. The superconducting properties were investigated by fundamental and third harmonic AC magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…In figure 1(a), the XRD patterns displayed are of the Ag-added FeSe 0.94 for wires 1, 2, 3 and include the data of the precursor for comparison. It can be observed that most of the reflection peaks are well indexed to the tetragonal crystal structure with space group P4/nmm for the precursor, and all wires are in agreement within earlier reports [24,25]. However, in the precursor and wire 3, an additional reflection peak appeared at about 2θ = 31 • , which belongs to the δ-FeSe phase with space group P6 3 /mmc.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In figure 1(a), the XRD patterns displayed are of the Ag-added FeSe 0.94 for wires 1, 2, 3 and include the data of the precursor for comparison. It can be observed that most of the reflection peaks are well indexed to the tetragonal crystal structure with space group P4/nmm for the precursor, and all wires are in agreement within earlier reports [24,25]. However, in the precursor and wire 3, an additional reflection peak appeared at about 2θ = 31 • , which belongs to the δ-FeSe phase with space group P6 3 /mmc.…”
Section: Resultssupporting
confidence: 89%
“…Metal additives are one of the techniques used to overcome these challenges for both conventional and nonconventional superconductors. The introduction of silver into Fe(Se, Te) superconducting polycrystalline has been proven to improve its structural and superconducting properties [24][25][26][27][28][29][30][31]. It was reported that silver develops intra-and intergrain connectivity and enhances the critical parameters like the superconducting transition temperature (T c ), current density (J c ), upper critical field (H c2 ), irreversibility field (H irr ) and the screening ability, pinning, activation energy and chemical phase stability.…”
Section: Introductionmentioning
confidence: 99%
“…where T * is the temperature where the investigated phenomenon is no more detectable. Thanks to the fitting procedure, it can be noted that the H irr values for T = 4 K, which is typically considered for power applications of superconductivity, are in the range of about 30 ÷ 40 Tesla in agreement with the ones present in literature for 11 family samples [9,[78][79][80][81] and other sample types [82][83][84][85][86]. In particular, the H irr value at T = 4 K for ν = 9693 Hz is equal to 42 Tesla which approaches the maximum value reported by Hosono et al [9].…”
Section: Resultssupporting
confidence: 72%
“…Moreover, a small amount of Ag was found to enter into the crystal structure of FeSe 0.5 Te 0.5 . We established that the Ag addition in FeSe 0.94 improves both the intra-and inter-granular superconducting properties and slightly increases the irreversibility field [7]. Further investigations showed [8] that critical temperature, the magnetoresistance, the upper critical field and the activation energy for thermally activated flux flow also increased as a result of 4 wt % Ag doping.…”
Section: Introductionmentioning
confidence: 73%